Cord blood bilirubin level as a predictor of development of pathological hyperbilirubinemia in new-borns - Pradhan, Ashish; Lamichaney, Rachna; Sharma, Vibhu (International Journal of Contemporary Pediatrics, 2017)
Background: There may be a delay in recognition of pathological hyperbilirubinemia which may lead to serious consequences in the new born. The purpose of this study was to verify whether the cord bilirubin levels predicted the development of pathological hyperbilirubinemia. Methods: In this hospital based prospective cross-sectional study conducted at Central Referral Hospital, Gangtok from December 2014 to November 2015, 202 live new born meeting the inclusion criteria were enrolled. After birth, cord blood was collected for the estimation of cord blood bilirubin and the babies were followed up daily for the development of clinical jaundice. Peripheral venous blood was collected for the estimation of serum bilirubin levels in those who developed clinical jaundice. Results: The incidence of pathological hyperbilirubinemia in our study is 12.87%. The mean gestational age is 38.3 weeks. There is a significant association between cord blood total bilirubin levels and the development of pathological hyperbilirubinemia in newborns with a P-value of 0.000. A critical cord bilirubin level ≥ 2.50mg/dl has sensitivity of 84.1%, specificity of 88.5%, positive predictive value of 98% and negative predictive value of 45.1% for predicting the risk of developing pathological jaundice. Conclusions: This study concludes that cord blood total bilirubin levels reliably predict the occurrence of pathological hyperbilirubinemia as defined by current operational guidelines.